2014
DOI: 10.1016/j.stem.2014.11.009
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiac Repair in a Porcine Model of Acute Myocardial Infarction with Human Induced Pluripotent Stem Cell-Derived Cardiovascular Cells

Abstract: Summary Human induced pluripotent stem cells (hiPSCs) hold promise for myocardial repair following injury, but preclinical studies in large animal models are required to determine optimal cell preparation and delivery strategies to maximize functional benefits and to evaluate safety. Here, we utilized a porcine model of acute myocardial infarction (MI) to investigate the functional impact of intramyocardial transplantation of hiPSC-derived cardiomyocytes, endothelial cells, and smooth muscle cells, in combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
341
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 409 publications
(354 citation statements)
references
References 29 publications
11
341
1
1
Order By: Relevance
“…Okano and colleagues (236) and Bursac and colleagues (211) later demonstrated that the functional and structural properties of engineered mouse heart tissue could be significantly improved by combining stem cell-derived cardiomyocytes with noncardiomyocytes. Similarly, Ye et al (405) showed in a porcine model of MI that transplantation of engineered contractile heart tissue composed of a mixture of human iPSC-derived cardiomyocytes, endothelial cells, and smooth muscle cells is therapeutically superior to using hiPSC cardiomyocytes alone. More recently, Burridge et al (39) demonstrated that the contractility of engineered human heart tissue from iPSC-derived cardiomyocytes may be significantly improved in the presence of endothelial cells and MSCs.…”
Section: Clinical Application Of Engineered Heart Tissuementioning
confidence: 92%
See 2 more Smart Citations
“…Okano and colleagues (236) and Bursac and colleagues (211) later demonstrated that the functional and structural properties of engineered mouse heart tissue could be significantly improved by combining stem cell-derived cardiomyocytes with noncardiomyocytes. Similarly, Ye et al (405) showed in a porcine model of MI that transplantation of engineered contractile heart tissue composed of a mixture of human iPSC-derived cardiomyocytes, endothelial cells, and smooth muscle cells is therapeutically superior to using hiPSC cardiomyocytes alone. More recently, Burridge et al (39) demonstrated that the contractility of engineered human heart tissue from iPSC-derived cardiomyocytes may be significantly improved in the presence of endothelial cells and MSCs.…”
Section: Clinical Application Of Engineered Heart Tissuementioning
confidence: 92%
“…The first category includes myocardial transplantation of cell types with unequivocal myogenic ability, such as uncommitted induced pluripotent stem cells (iPSC) or embryonic stem cells (ESC) (22), iPSC/ESC-derived human cardiomyocytes (61,97,304,405), or ESC/iPSC-derived cardiomyocyte precursors (97, 240,405). Gene therapy-based approaches aiming at converting scar tissue fibroblasts into cardiomyocyte-like cells (288,340) or forcing massive dedifferentiation and proliferation of surviving cardiomyocytes (68,95) are also under consideration, although still far from clinical application due to concerns over safety and technical feasibility (87).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…hESCs and iPSCs differentiate robustly into a highly purified population of functional cardiac myocytes in vitro 12, 13 . Functional improvement of the injured myocardium has been observed in murine, rodent, and porcine models that received either hESCs-derived cardiac myocytes (hCMs) 12, 14-20 or iPSCs-derived cardiac myocytes (iCMs) 21, 22 . Additionally, pluripotent stem cell-derived cardiac myocytes have been shown to engraft and improve heart function more effectively than non-cardiac derivatives 12, 17-19 .…”
Section: Introductionmentioning
confidence: 99%
“…Injection of iPS-derived cardiac myocytes, smooth muscle cells, and endothelial cells demonstrated engraftment of all cell types (128). Interestingly, there were significant improvements in LV function despite relatively low rates of engraftment compared with earlier studies using ES cell-derived cardiac myocytes in nonhuman primates (21).…”
Section: Induced Pluripotent Stem Cellsmentioning
confidence: 71%